Method for improving fatigue performance of additive manufacturing titanium alloy
By optimizing additive manufacturing process parameters and performing stress annealing, shot peening and coating applications, the problem of poor fatigue performance of additive manufacturing titanium alloy parts is solved, which significantly improves fatigue performance and service life, and expands its application areas.
Patent Information
- Application Number
- CN202411834401.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The fatigue performance of additively manufactured titanium alloy parts is poor, mainly due to internal pores, unfusion defects, residual stress and uneven grain structure.
Improve the internal structure and surface characteristics of titanium alloy parts by optimizing additive manufacturing process parameters such as laser power, scanning speed, scanning spacing and powder thickness, combined with stress annealing, shot peening and applications of ceramic or metal coatings.
It significantly improves the fatigue performance of additively manufactured titanium alloys, extends service life, reduces safety risks and maintenance costs caused by fatigue failure, and gives it a wider application prospect in fields such as aerospace and biomedicine.
Smart Images

Figure CN119549749A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of additive manufacturing, and in particular to a method for improving fatigue performance of an additively manufactured titanium alloy. Background Art
[0002] Additive manufacturing technology has unique advantages in the manufacturing of titanium alloy parts and can achieve rapid prototyping of complex structures.
[0003] However, additively manufactured titanium alloys often have poor fatigue performance, which is mainly caused by factors such as pores, unfused defects, residual stress, and uneven grain structure. These defects and poor structures can easily become crack sources under cyclic loads, thereby significantly reducing the fatigue life of titanium alloys and limiting the wide application of additively manufactured titanium alloys in aerospace, biomedicine and other fields with high fatigue performance requirements. Therefore, it is of great practical significance to develop an effective method to improve the fatigue performance of additively manufactured titanium alloys. Summary of the invention
[0004] The present invention provides a method for improving fatigue performance of titanium alloy manufactured by additive manufacturing, so as to solve the shortcomings of the background technology.
[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is: A method for improving fatigue performance of an additively manufactured titanium alloy, comprising the following steps: Step S100, optimizing additive manufacturing process parameters such as laser power, scanning speed, scanning spacing, and powder thickness through a combination of a large number of experiments and numerical simulations to obtain minimum porosity and optimal fusion effect; Step S200, subjecting the additively manufactured titanium alloy part to stress relief annealing in a vacuum or inert gas protective atmosphere; Step S300: Shot peening is performed on the parts to effectively inhibit the initiation and expansion of surface cracks, while refining the surface grains and improving the surface hardness and strength.
[0006] Furthermore, after step S300, step S400 is performed to prepare a ceramic coating or a metal coating on the surface of the titanium alloy part after the above treatment.
[0007] Further, in step S100, the laser power is gradually adjusted within a certain range, and indicators such as the stability of the molten pool, the size of the molten pool, and the density of the molded part are monitored at the same time to determine the laser power range that can obtain the minimum porosity and the best fusion effect; the scanning speed is optimized in a similar way to avoid unfusion defects caused by too fast scanning speed or excessive heat accumulation causing coarse grains due to too slow scanning speed; the scanning spacing is adjusted to ensure good bonding between adjacent melt channels and reduce interlayer defects; the powder thickness is controlled to ensure that the powder is evenly laid and can be fully melted under the action of the laser.
[0008] Furthermore, specifically, it was experimentally determined that the laser power was 200 W, the scanning speed was 1000 mm / s, the scanning spacing was 0.1 mm, and the powder thickness was 0.04 mm. Under this parameter, the density of the molded specimen reached more than 98%, and the porosity was significantly reduced.
[0009] Further, in step 200, specifically, the annealing temperature is set between 550°C and 650°C, the holding time is 2 to 4 hours, and then cooled to room temperature at a cooling rate of 50 to 100°C / h; this step can effectively reduce the residual stress inside the part and reduce the risk of crack initiation caused by residual stress.
[0010] Further, in step 300, specifically, shot peening is performed on the surface of the titanium alloy part using a shot with a hardness of 45 to 55 HRC and a diameter of 0.3 to 0.5 mm, a spray pressure of 0.3 to 0.5 MPa and a coverage rate of 100% to 200%.
[0011] Further, in step S300, recrystallization annealing is performed after stress relief annealing; the annealing temperature is controlled at 750°C to 850°C, and the holding time is 1 to 3 hours, so that the grains inside the titanium alloy are recrystallized, the grain structure is refined, and the strength and toughness of the material are further improved, thereby indirectly improving the fatigue performance.
[0012] Furthermore, ultrasonic impact treatment is performed after shot peening to improve the residual stress state of the part surface, make the surface structure more uniform and dense, and further improve fatigue performance; specifically, the ultrasonic impact frequency is set at 20 to 30 kHz, the impact energy is 20 to 40 J, and the treatment time is 5 to 10 minutes.
[0013] The beneficial effects of the present invention are: The fatigue performance improvement method of additively manufactured titanium alloy of the present invention has a comprehensive effect from multiple aspects such as internal structure optimization, residual stress elimination, surface strengthening and corrosion protection, which significantly improves the fatigue performance of additively manufactured titanium alloy, making it have a wider application prospect in aerospace, biomedicine and other fields with strict requirements on fatigue performance, improving the reliability and service life of the product, and reducing the safety risks and maintenance costs caused by fatigue failure. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a flowchart of the steps of Embodiment 1. DETAILED DESCRIPTION
[0015] In order to make the contents of the present invention more clearly understood, the technical solutions in the embodiments of the present invention are described clearly and completely. Example
[0016] A method for improving fatigue performance of an additively manufactured titanium alloy, comprising the following steps: Step S100: By combining a large number of experiments with numerical simulations, the additive manufacturing process parameters such as laser power, scanning speed, scanning spacing, and powder thickness are optimized to obtain the minimum porosity and the best fusion effect.
[0017] Among them, the laser power is gradually adjusted within a certain range, and the stability of the molten pool, the size of the molten pool, and the density of the molded parts are monitored at the same time to determine the laser power range that can obtain the minimum porosity and the best fusion effect; the scanning speed is optimized in a similar way to avoid the defects of unfusion caused by too fast scanning speed or the excessive heat accumulation caused by too slow scanning speed to produce coarse grains; the scanning spacing is adjusted to ensure good bonding between adjacent melt channels and reduce interlayer defects; the powder thickness is controlled to ensure that the powder is evenly laid and can be fully melted under the action of the laser. Specifically, after experiments, it was determined that the laser power was 200W, the scanning speed was 1000mm / s, the scanning spacing was 0.1mm, and the powder thickness was 0.04mm. Under this parameter, the density of the molded specimen reached more than 98%, and the porosity was significantly reduced.
[0018] The titanium alloy parts after additive manufacturing are subjected to stress relief annealing in a vacuum or inert gas atmosphere. The annealing temperature is set between 550℃ and 650℃, the holding time is 2 to 4 hours, and then cooled to room temperature at a cooling rate of 50 to 100℃ / h. This step can effectively reduce the residual stress inside the parts and reduce the risk of crack initiation caused by residual stress.
[0019] Shot peening of parts can effectively inhibit the initiation and expansion of surface cracks, while refining surface grains and improving surface hardness and strength. Specifically, the surface of titanium alloy parts is shot peened with a hardness of 45-55HRC and a diameter of 0.3-0.5mm, a spray pressure of 0.3-0.5MPa and a coverage rate of 100%-200%.
[0020] A layer of ceramic coating or metal coating is prepared on the surface of the titanium alloy part after the above treatment. For example, the alumina ceramic coating is prepared by plasma spraying technology, and the coating thickness is between 80 and 120 μm. The coating can act as a physical barrier to prevent the external environment from corroding the titanium alloy substrate and reduce the occurrence of corrosion fatigue. At the same time, the interface bonding force between the coating and the substrate can effectively transfer the load and further improve the overall fatigue performance of the part.
[0021] In summary, the method for improving fatigue performance of additively manufactured titanium alloy of the present invention has a comprehensive effect from multiple aspects such as internal structure optimization, residual stress elimination, surface strengthening and corrosion protection, which significantly improves the fatigue performance of additively manufactured titanium alloy, making it have a wider application prospect in aerospace, biomedicine and other fields with strict requirements on fatigue performance, improving the reliability and service life of the product, and reducing the safety risks and maintenance costs caused by fatigue failure. Example
[0022] A method for improving fatigue performance of an additively manufactured titanium alloy, comprising the following steps: Step S100: By combining a large number of experiments with numerical simulations, the additive manufacturing process parameters such as laser power, scanning speed, scanning spacing, and powder thickness are optimized to obtain the minimum porosity and the best fusion effect.
[0023] Among them, the laser power is gradually adjusted within a certain range, and the stability of the molten pool, the size of the molten pool, and the density of the molded parts are monitored at the same time to determine the laser power range that can obtain the minimum porosity and the best fusion effect; the scanning speed is optimized in a similar way to avoid the defects of unfusion caused by too fast scanning speed or the excessive heat accumulation caused by too slow scanning speed to produce coarse grains; the scanning spacing is adjusted to ensure good bonding between adjacent melt channels and reduce interlayer defects; the powder thickness is controlled to ensure that the powder is evenly laid and can be fully melted under the action of the laser. Specifically, after experiments, it was determined that the laser power was 200W, the scanning speed was 1000mm / s, the scanning spacing was 0.1mm, and the powder thickness was 0.04mm. Under this parameter, the density of the molded specimen reached more than 98%, and the porosity was significantly reduced.
[0024] The titanium alloy parts after additive manufacturing are subjected to stress relief annealing in a vacuum or inert gas protective atmosphere. The annealing temperature is set between 550℃ and 650℃, the holding time is 2 to 4 hours, and then cooled to room temperature at a cooling rate of 50 to 100℃ / h. This step can effectively reduce the residual stress inside the parts and reduce the risk of crack initiation caused by residual stress. Preferably, it is also possible to perform: recrystallization annealing after stress relief annealing. The annealing temperature is controlled at 750℃ to 850℃, and the holding time is 1 to 3 hours, so that the grains inside the titanium alloy are recrystallized, the grain structure is refined, and the strength and toughness of the material are further improved, thereby indirectly improving the fatigue performance.
[0025] Shot peening of parts can effectively inhibit the initiation and expansion of surface cracks, while refining the surface grains and improving the surface hardness and strength. Specifically, a shot with a hardness of 45-55HRC and a diameter of 0.3-0.5mm is used to shot peen the surface of titanium alloy parts at a spray pressure of 0.3-0.5MPa and a coverage rate of 100%-200%. Preferably, it is also possible to perform ultrasonic impact treatment after shot peening to improve the residual stress state of the surface of the parts, make the surface structure more uniform and dense, and further improve fatigue performance. Specifically, the ultrasonic impact frequency is set at 20-30kHz, the impact energy is 20-40J, and the treatment time is 5-10 minutes.
[0026] A layer of ceramic coating or metal coating is prepared on the surface of the titanium alloy part after the above treatment. For example, the alumina ceramic coating is prepared by plasma spraying technology, and the coating thickness is between 80 and 120 μm. The coating can act as a physical barrier to prevent the external environment from corroding the titanium alloy substrate and reduce the occurrence of corrosion fatigue. At the same time, the interface bonding force between the coating and the substrate can effectively transfer the load and further improve the overall fatigue performance of the part.
[0027] In summary, the method for improving fatigue performance of additively manufactured titanium alloy of the present invention has a comprehensive effect from multiple aspects such as internal structure optimization, residual stress elimination, surface strengthening and corrosion protection, which significantly improves the fatigue performance of additively manufactured titanium alloy, making it have a wider application prospect in aerospace, biomedicine and other fields with strict requirements on fatigue performance, improving the reliability and service life of the product, and reducing the safety risks and maintenance costs caused by fatigue failure.
[0028] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for improving fatigue performance of titanium alloy by additive manufacturing, characterized in that: The following steps are involved: Step S100, optimizing the additive manufacturing process parameters of laser power, scanning speed, scanning spacing, and powder thickness through a combination of a large number of experiments and numerical simulations to obtain the minimum porosity and the best fusion effect; Step S200, subjecting the additively manufactured titanium alloy part to stress relief annealing in a vacuum or inert gas protective atmosphere; Step S300: Shot peening is performed on the parts to effectively inhibit the initiation and expansion of surface cracks, while refining the surface grains and improving the surface hardness and strength.
2. The method for improving fatigue performance of titanium alloy by additive manufacturing according to claim 1, characterized in that: After step S300, step S400 is performed to prepare a ceramic coating or a metal coating on the surface of the titanium alloy part after the above treatment.
3. The method for improving fatigue performance of titanium alloy by additive manufacturing according to claim 1, characterized in that: In step S100, the laser power is gradually adjusted within a certain range, and the stability of the molten pool, the size of the molten pool and the density index of the molded part are monitored at the same time to determine the laser power range that can obtain the minimum porosity and the best fusion effect; the scanning speed is optimized in a similar way to avoid unfusion defects caused by too fast scanning speed or excessive heat accumulation causing coarse grains due to too slow scanning speed; the scanning spacing is adjusted to ensure good bonding between adjacent melt channels and reduce interlayer defects; the powder thickness is controlled to ensure that the powder is evenly laid and can be fully melted under the action of the laser.
4. The method for improving fatigue performance of titanium alloy by additive manufacturing according to claim 3, characterized in that: Specifically, experiments have determined that the laser power is 200W, the scanning speed is 1000mm / s, the scanning spacing is 0.1mm, and the powder thickness is 0.04mm. Under this parameter, the density of the molded specimen reaches more than 98%, and the porosity is significantly reduced.
5. The method for improving fatigue performance of titanium alloy by additive manufacturing according to claim 1, characterized in that: In step 200, specifically, the annealing temperature is set between 550°C and 650°C, the holding time is 2 to 4 hours, and then cooled to room temperature at a cooling rate of 50 to 100°C / h; this step can effectively reduce the residual stress inside the part and reduce the risk of crack initiation caused by residual stress.
6. The method for improving fatigue performance of titanium alloy by additive manufacturing according to claim 1, characterized in that: In step 300, specifically, shot peening is performed on the surface of the titanium alloy part using a shot with a hardness of 45-55 HRC and a diameter of 0.3-0.5 mm, a spray pressure of 0.3-0.5 MPa and a coverage rate of 100%-200%.
7. The method for improving fatigue performance of titanium alloy by additive manufacturing according to claim 1, characterized in that: In step S300, recrystallization annealing is performed after stress relief annealing; the annealing temperature is controlled at 750°C to 850°C, and the holding time is 1 to 3 hours, so that the grains inside the titanium alloy are recrystallized, the grain structure is refined, and the strength and toughness of the material are further improved, thereby indirectly improving the fatigue performance.
8. The method for improving fatigue performance of titanium alloy by additive manufacturing according to claim 2, characterized in that: Ultrasonic impact treatment is performed after shot peening to improve the residual stress state on the surface of the parts, make the surface structure more uniform and dense, and further improve the fatigue performance; specifically, the ultrasonic impact frequency is set at 20-30kHz, the impact energy is 20-40J, and the treatment time is 5-10 minutes.
Citation Information
Patent Citations
Method for eliminating residual stress in welding by ultrasonic peening and use thereof
CN102002581A
Surface enhancement processing method of titanium alloy blade disc blade and application of method
CN115466912A
Method for improving fatigue performance of titanium alloy through micro-scale laser strengthening
CN118663923A
Calculation method for optimizing additive manufacturing alloy components
CN118821561A
Method and device for generating control data for an additive manufacturing device
US20210245251A1
Cited By
Additive manufacturing metal piece and surface composite strengthening method and tool thereof
CN122644608A
A method for predicting the structure of a powder-fed titanium alloy and regulating fatigue performance
CN122850806A